In utero exposure to organochlorine pesticides and early menarche in the Avon Longitudinal Study of Parents and Children. (September 2016) - Namulanda, Gonza; Maisonet, Mildred; Taylor, Ethel; Flanders, W. Dana; Olson, David; Sjodin, Andreas; Qualters, Judith R.; Vena, John; Northstone, Kate; Naeher, Luke
Abstract: Introduction: Epidemiologic data supporting the role of organochlorine pesticides in pubertal development are limited. Methods: Using a nested case-control design, serum collected during pregnancy from mothers of 218 girls who reported menarche before 11.5 years of age (cases) and 230 girls who reported menarche at or after 11.5 years of age (controls) was analyzed for 9 organochlorines and metabolites. We analyzed the association between in utero organochlorine concentrations and early menarche using multivariate logistic regression controlling for mother's age at menarche, or mother's prenatal BMI. Results: We did not observe an association between in utero exposure to HCB, β-HCH, ϒ-HCH, p, p′-DDT, p, p′-DDE, oxychlordane or trans-nonachlor and early menarche. Conclusions: This study is the first to examine the association between in utero exposure to HCB, β-HCH, ϒ-HCH, oxychlordane or trans-nonachlor and early menarche. In utero exposure to organochlorine pesticides does not appear to have a role in the timing of menarche in this study. Highlights: Organochlorine pesticides (OCPs) are still detected in populations despite bans. The association between in utero exposure to OCPs and early menarche is examined. No association was found between in utero exposure to OCPs and early menarche.